Adaptation and Utilization of Flipped Learning Strategy of Mathematics Teachers - Buenafe, Marjeric; Gallos, Julius; Aseron, Trina; Borabien, Nicole; Martinez, Jonalyn; Canosa, Jamaica Maribeth; Bautista, Harren James; De Ramos, Lovelita; Hernandez, Lyra Crizelle (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigated the adaptation and utilization of flipped learning strategies among Mathematics teachers at Governor Feliciano Leviste Memorial National High School, grounded in the principles of learner-centered instruction to enhance student engagement, independence, and mathematical proficiency. Anchored on the flipped learning framework, the study employed a descriptive quantitative research design, utilizing a validated researcher-made survey administered to 355 junior high school students across Grades 7 to 10, selected through stratified random sampling. The research examined teachers’ adaptation of flipped learning strategies in terms of educational technology and learning through activities, as well as the extent of their utilization relative to conceptual understanding, procedural fluency, strategic competency, adaptive reasoning, and productive disposition. Results revealed that teachers highly adapted flipped learning strategies, particularly through the use of online and offline materials, video lectures, interactive modules, and technology-supported activities, which facilitated active learning and improved student mathematical performance. The extent of utilization was found to be moderate across all dimensions, indicating effectiveness tempered by challenges such as device accessibility and multimedia engagement. Significant positive relationships were established between the strategies adapted and the flipped learning strategies utilized by the teachers, confirming the impact of technology and structured activities on student learning outcomes. Based on these findings, the study recommended the development of an interactive Math Flip Book, institutional support for teacher training, and the provision of resources to foster a positive, engaging, and supportive learning environment. The study aligns with Sustainable Development Goal 4, promoting quality education through innovative teaching strategies that enhance critical thinking, problem-solving, and digital literacy. Its sustainability impact lies in strengthening educational practices, improving student learning outcomes, and providing a replicable model for effective mathematics instruction in technology-enhanced learning environments.
Keywords: Adaptive Reasoning; Conceptual Understanding; Educational Technology; Flipped Learning; Learning-Through-Activities; Mathematical Proficiency; Procedural Fluency; Productive Disposition; Strategic Competency; Student Engagement